Euro effects on the intensive and extensive margins of trade - Harry Flam; Håkan Nordström (Center for Economic Studies and ifo Institute (CESifo), 2006)
We estimate that the euro has increased trade within the eurozone by about 26 per cent and trade between the eurozone and outsiders by about 12 per cent on average for the years 2002- 2005 compared to 1995-1998. The percentage increases were smaller for products that were exported every year during the sample period than for products that were not, indicating significant and substantial effects on the extensive margin of trade. The euro effects were concentrated to semi-finished and finished products, in particular to industries with highly processed products such as pharmaceuticals and machinery.
Keywords: F1; 330; Europäische Wirtschafts- und Währungsunion; Euro; Außenhandelskontingent; Industrieprodukt; Wirtschaftspolitische Wirkungsanalyse; EU-Staaten